2015
DOI: 10.1590/0037-8682-0257-2014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for late diagnosis of HIV infection in Brazilian infants and children

Abstract: Introduction: Late human immunodefi ciency virus (HIV) diagnosis is an important cause of HIV-related morbidity and mortality in infants and children. Methods: This retrospective cohort study of HIV-infected children diagnosed in Sergipe, in northeastern Brazil, between 2002 and 2011 aimed to determine the prevalence of and risk factors for late HIV diagnosis. Results: Of 55 infants and children with confi rmed infection, 42 (76.5%) were diagnosed at ≥ 12 months old. No antiretroviral prophylaxis during delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…The absence of this information suggests flaws in the follow-up care routines of newborns exposed to HIV. Local studies have reported late diagnosis of HIV in children [ 29 ] and follow-up losses that can reach 30% in some places in the country [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of this information suggests flaws in the follow-up care routines of newborns exposed to HIV. Local studies have reported late diagnosis of HIV in children [ 29 ] and follow-up losses that can reach 30% in some places in the country [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This bad news is communicated between adults at a time when the child is already sick and has been hospitalized for a while. This means that antiretroviral treatment starts with a delay, contributing to increased morbidity and mortality (Johnson et al., ; Lemos, Anglemyer, Santos, Gurgel, & Rutherford, ; Wamalwa et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Lemos et al. (), the value of family participation in caring for the person with HIV/aids was identified, as the family considers him/her as the centre of care. In this study, family members cited the importance of nurses, psychologists and physicians in nonsystematic consultations about the disclosure of HIV to the children.…”
Section: Discussionmentioning
confidence: 99%
“…1 These delays result in missed opportunities for timely antiretroviral therapy (ART) initiation and are a significant cause of HIV-related pediatric morbidity and mortality. 5 , 6 Indeed, late provision of HIV care and treatment undermines the benefits of ART and compromises survival. 7 Globally, 46% of the world's 1.7 million children living with HIV (CLHIV) were not on lifesaving treatment in 2020.…”
Section: Introductionmentioning
confidence: 99%